Comparison of different in situ measurements techniques of intelligibility in an open-plan office. Issue 2 (June 2018) - D'Orazio, Dario; Rossi, Elena; Garai, Massimo
Acoustic comfort in open-plan offices is a relatively recent research topic and some practices have not yet been consolidated. The goal in these spaces is to achieve good speech privacy at every workstation, reaching a high value of spatial decay of the sound pressure level. In case of refurbishment, a proper measurement of intelligibility criteria is needed, for example, in order to properly calibrate a numerical model or to plan acoustic treatments. This work compares different measurement techniques to evaluate the spatial distribution of intelligibility criteria. In situ measurements were done in an open-plan office used as a case study. Both omnidirectional and directional sound sources with different sound power levels were used, according, respectively, to ISO 3382-3:2012 and ITU-T P.51:1996. Furthermore, compensation algorithms were used in impulse response measurements in presence of Heating, Ventilation and Air Conditioning noise. The study shows, in a preliminary way, how different techniques and equipment can influence intelligibility criteria used in the open-plan office characterization. Results show that the indirect method of measuring Speech Transmission Index could not be used when the background level is high as the case study while the direct method returns good results.